2005
DOI: 10.1007/s00402-005-0812-8
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraobserver assessment of periacetabular osteodensitometry after cemented and uncemented total hip arthroplasty using computed tomography

Abstract: In conclusion, the periacetabular bone density measurement as conducted in this CT study is a new reproducible method for in vivo evaluation of cortical and cancellous pelvic bone after cemented and uncemented acetabular cup implantation. In vivo CT measurements will allow a thorough assessment of periacetabular stress-shielding phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…[2][3][4][5][6][7]11,[15][16][17] To allow a differentiated three-dimensional analysis of cortical and cancellous bone structures after THA in vivo we have introduced a novel method of CT-assisted osteodensitometry. 9,10,13,14 In a previous study we have provided clear evidences for the reproducibility and validity of our method. 9 Opposed to DXA CT-assisted osteodensitometry allows the separate analysis of cortical and cancellous BD surrounding the prosthesis, which might be a potential advantage in studying mechanical load transfer mechanisms to the ilium after total hip arthroplasty.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…[2][3][4][5][6][7]11,[15][16][17] To allow a differentiated three-dimensional analysis of cortical and cancellous bone structures after THA in vivo we have introduced a novel method of CT-assisted osteodensitometry. 9,10,13,14 In a previous study we have provided clear evidences for the reproducibility and validity of our method. 9 Opposed to DXA CT-assisted osteodensitometry allows the separate analysis of cortical and cancellous BD surrounding the prosthesis, which might be a potential advantage in studying mechanical load transfer mechanisms to the ilium after total hip arthroplasty.…”
mentioning
confidence: 60%
“…9,10,13,14 In a previous study we have provided clear evidences for the reproducibility and validity of our method. 9 Opposed to DXA CT-assisted osteodensitometry allows the separate analysis of cortical and cancellous BD surrounding the prosthesis, which might be a potential advantage in studying mechanical load transfer mechanisms to the ilium after total hip arthroplasty. 13,14 A DXA based study by Sabo et al 11 showed a decrease of periacetabular BD 24 months after implantation of a rigid press fit cup.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Using sectional CT imaging, a separate analysis of cortical and cancellous bone structures can be achieved [17,18]. The CT-assisted osteodensitometry technology used in this study is accurate and reproducible [16,19]. We found BD loss ranging from −17% to −0.9% in the cortical bone and ranging from −22% to −4% in the cancellous bone.…”
Section: Discussionmentioning
confidence: 91%